Implementation of Research Learning Using Learning Tools Padlet to Develop Early Childhood HOTS Skills - Rusliah; Budiarti, Erna (Kirana Publisher (KNPub), 2024)
Students who are educated with HOTS are able to apply what they have in new situations. The purpose of this study is to find out the description of how to implement research in early childhood by using Padlet learning tools so that it can develop HOTS skills in learning. The research was conducted at TKIT Nurul Fikri, West Java. Data collection techniques were carried out by observation, interviews, and documentation. The data analysis technique used the Miles Huberman model. HOTS skills developed in research learning using Padlet are analysis, evaluation, and creation. The stages of research learning are making observations, making research questions, making research designs, making research sheets, carrying out, and communicating research results. Research learning using padlets motivates children to complete their tasks, breaks boredom, and creates an emotional connection with the material and can be well documented.